1988
DOI: 10.1177/096032718802000401
|View full text |Cite
|
Sign up to set email alerts
|

Visual performance using reaction times

Abstract: /npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr Access and use of this website and the material on it are subject to the Terms and Conditions set forth at http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/jsp/nparc_cp.jsp?lang=en NRC Publications Archive Archives des publications du CNRCThis publication could be one of several versions: author's original, accepted manuscript or the publisher's version. / La version de cette publication peut être l'une des suivantes : la version prépubli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(58 citation statements)
references
References 12 publications
5
53
0
Order By: Relevance
“…An alternative explanation for the reduced visibility ofthe dark stimulus may be the fact that it depended mainly on off centre ganglion cells, which in the central field are less abundant than on centre ganglion cells (that is, in a ratio of approximately 1-2:3). Similar psychophysical differences between these two parallel visual pathways have previously been reported for foveal vision with regard to target detection rates and reaction times.23 24 In addition, electrophysiological differences between these two channels have been observed.2526 We are unaware of a previous report of perimetric asymmetries between on and off pathways. If the black perimetric stimulus is indeed testing the off pathway, it may prove to be superior to conventional luminous stimuli.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…An alternative explanation for the reduced visibility ofthe dark stimulus may be the fact that it depended mainly on off centre ganglion cells, which in the central field are less abundant than on centre ganglion cells (that is, in a ratio of approximately 1-2:3). Similar psychophysical differences between these two parallel visual pathways have previously been reported for foveal vision with regard to target detection rates and reaction times.23 24 In addition, electrophysiological differences between these two channels have been observed.2526 We are unaware of a previous report of perimetric asymmetries between on and off pathways. If the black perimetric stimulus is indeed testing the off pathway, it may prove to be superior to conventional luminous stimuli.…”
Section: Resultssupporting
confidence: 52%
“…Similar psychophysical differences between these two parallel visual pathways have previously been reported for foveal vision with regard to target detection rates and reaction times. 23 24 In addition, electrophysiological differences between these two channels have been observed. 2526 We are unaware of a previous report of perimetric asymmetries between on and off pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have, including Shlaer, whom they cite. Such studies of visual performance for fixed pupil sizes show that visual performance improves with higher light levels (e.g., Rea and Ouellette, 1988). In fact, the data reported by the authors in Figure 8 contradict, indirectly at least, their own conclusions.…”
mentioning
confidence: 85%
“…Colombo, Kirschbaum, and Raitelli suggested that a fifth variable, blur, be added to the visual performance model. 21 Visibility measured using reaction times to a visual stimulus [22][23][24] and the time required to perform a number-checking task 20 have contributed to this understanding. Visibility is poor when the task luminance is low, but above a certain level of stimulation it quickly saturates.…”
Section: Biopsychological Processes In Lighting-behavior Relationshipmentioning
confidence: 99%